The teachings of Syrianus on Plato's Timaeus and Parmenides - Wear, Sarah Klitenic. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2011)
Although it has long been established that Syrianus, the teacher of Proclus, was the source of much of his student's metaphysics, it is not known precisely what in Proclus' thought can be attributed to Syrianus. The problem is compounded by the fact that Syrianus wrote very little and there is uncertainty as to whether written commentaries ever existed of his teaching on Plato's Timaeus and Parmenides , the most important sources for Platonic metaphysics. This work attempts to re-construct the major tenets of Syrianus' philosophical teachings on the Timaeus and Parmenides based on the testimonia of Proclus, as found in Proclus' commentaries on Plato's Timaeus and Parmenides and, Damascius, as reported in his On First Principles and commentary on Plato's Parmenides .